Regulatory T cell suppressive potency dictates the balance between bacterial proliferation and clearance during persistent Salmonella infection. - Tanner M Johanns; James M Ertelt; Jared H Rowe; Sing Sing Way (PLoS Pathogens)
The pathogenesis of persistent infection is dictated by the balance between opposing immune activation and suppression signals. Herein, virulent Salmonella was used to explore the role and potential importance of Foxp3-expressing regulatory T cells in dictating the natural progression of persistent bacterial infection. Two distinct phases of persistent Salmonella infection are identified. In the first 3-4 weeks after infection, progressively increasing bacterial burden was associated with delayed effector T cell activation. Reciprocally, at later time points after infection, reductions in bacterial burden were associated with robust effector T cell activation. Using Foxp3(GFP) reporter mice for ex vivo isolation of regulatory T cells, we demonstrate that the dichotomy in infection tempo between early and late time points is directly paralleled by drastic changes in Foxp3(+) Treg suppressive potency. In complementary experiments using Foxp3(DTR) mice, the significance of these shifts in Treg suppressive potency on infection outcome was verified by enumerating the relative impacts of regulatory T cell ablation on bacterial burden and effector T cell activation at early and late time points during persistent Salmonella infection. Moreover, Treg expression of CTLA-4 directly paralleled changes in suppressive potency, and the relative effects of Treg ablation could be largely recapitulated by CTLA-4 in vivo blockade. Together, these results demonstrate that dynamic regulation of Treg suppressive potency dictates the course of persistent bacterial infection.